1961
DOI: 10.1126/science.133.3466.1771
|View full text |Cite
|
Sign up to set email alerts
|

Response Latencies of Female Rats during Sexual Intercourse

Abstract: A female rat, by operating a lever, causes the presentation of a potent male rat and subsequent sexual contact. The female shows contact-response latencies that vary according to the nature of the contact. Latencies after ejaculations are longer than those after intromissions, which in turn exceed those after mounts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
59
0
4

Year Published

1973
1973
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(65 citation statements)
references
References 3 publications
2
59
0
4
Order By: Relevance
“…Using a bar-press response, Bermant (1961) replicated the ''pacing'' effect in which the latency of the female's postcopulatory return to the male increased as the intensity of the previous sexual encounter increased. Simple mounting was followed by short latencies to return to the male, whereas intromission and ejaculation were followed by longer latencies (Pierce & Nutall, 1961;see Erskine, 1989, for a review).…”
mentioning
confidence: 87%
“…Using a bar-press response, Bermant (1961) replicated the ''pacing'' effect in which the latency of the female's postcopulatory return to the male increased as the intensity of the previous sexual encounter increased. Simple mounting was followed by short latencies to return to the male, whereas intromission and ejaculation were followed by longer latencies (Pierce & Nutall, 1961;see Erskine, 1989, for a review).…”
mentioning
confidence: 87%
“…The behavioural mechanisms whereby the female receives appropriate cervical-vaginal stimu¬ lation for induction of pregnancy appear to involve patterns of approach toward and withdrawal from males which regulate or pace the intervals between intromissions (Bermant, 1961;Peirce & Nuttall, 1961;Schoelch-Krieger et ai, 1976;McClintock & Anisko, 1982;Erskine et ai, 1985Erskine et ai, , 1989. When experimental conditions allow the rat to pace her contacts with the male (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, intromission during 40 copulation correlates negatively with subsequent appetitive sexual behavior [9,15]. Instrumental responding analysis has shown that females that received mounts with intromission are slower to respond subsequently to a male than females that received mounts without intromission [3]. Although these data are equally consistent with the interpretation that sensory information relevant to intromission could have a consummatory value for the sexual appetite of the females [24,38], the MeA does not regulate partner 45 preference through modification of sexual motivation, because the lesioned females spent as much time nose poking as the sham operated females.…”
mentioning
confidence: 99%